An account of "the core" in economic theory - Jonathan Cogliano (Duke University, Center for the History of Political Economy (CHOPE), 2019)
The concept of 'the core' originates in cooperative game theory and its introduction to economics in the 1960s as a basis for proofs of existence of general equilibrium is one of the earliest attempts to use game theory to address big questions in economics. Discovery of the core was met with enthusiasm among the community of economic theorists at the time. However, use of the core eventually waned and the concept faded into the backdrop of economic theory. This paper makes use of unpublished correspondence between Herbert Scarf, Lloyd Shapley, and Martin Shubik, as well as other archival and secondary resources, to provide an account of the development of the core and the trajectory of this concept, including those who developed it, after its initial appearance. It is found that the core's eventual decline is explained by the combined effect of the slowing general equilibrium research program in the 1970s, the increasing prominence of non-cooperative game theory, and subtle issues with the concept that shaped Scarf and Shubik's research programs after the 1960s.
Keywords: B21; B23; B31; C70; C71; D50; 330; History of Economic Theory; the Core; Cooperative Game Theory; Herbert Scarf; Lloyd Shapley; Martin Shubik